An International Framework for Eco-Industrial Parks - United Nations Industrial Development Organization; World Bank Group; Deutsche Gesellschaft für Internationale Zusammenarbeit (World Bank, Washington, DC, 2017)
The aim of this publication is to provide an international framework (the “Framework”) with the minimum requirements and performance expectations as to how an industrial park can become an Eco-Industrial Park (EIP). It summarizes the key areas in which the three international organizations that have driven the development of this framework — including the United Nations Industrial Development Organisation (UNIDO), the World Bank Group, and Deutsche Gesellschaft für Internationale Zusammenarbeit GmbH (GIZ) — have aligned regarding what constitutes an Eco-Industrial Park (EIP). The International Framework for Eco-Industrial Parks will guide policymakers and practitioners on the critical elements that will help both governments and the private sector work together in establishing economically, socially and environmentally sustainable eco-industrial parks.